Elucidating on the drop impact dynamics of water-in-oil microemulsions via advanced rheometry; Colloids and Surfaces A: Physicochemical and Engineering Aspects; Vol. 720 - Mete M. Abbot; Yin F. Furui; Piskunov M. V. Maksim Vladimirovich; Roisman I. Ilia; Hussong J. Jeanette (2025, 2025)
Title screen